Squalene‐Hopene Cyclase: On the Polycyclization Reactions of Squalene Analogues Bearing Ethyl Groups at Positions C‐6, C‐10, C‐15, and C‐19. Issue 12 (30th March 2018) - Takahashi, Kazunari; Sasaki, Yusuke; Hoshino, Tsutomu
Abstract : Squalene‐hopene cyclase (SHC) has been found to convert acyclic squalene into 6, 6, 6, 6, 5‐fused pentacyclic triterpenes hopene and hopanol. The enzymatic reactions of squalene analogues bearing ethyl groups in lieu of methyl groups at positions C‐6, C‐10, C‐15, and C‐19 have been examined to investigate whether the larger ethyl substituents (a C1 unit increment) are accepted as substrates and to investigate how these substitutions affect polycyclization cascades. Analogue 6‐ethylsqualene19a did not cyclize, which indicates that substitution with the bulky group at C‐6 completely inhibited the polycyclization reaction. In contrast, 19‐ethylsqualene19b afforded a wide spectrum of cyclization products, including mono‐, bi‐, tetra‐, and pentacyclic products in a ratio of 6:6:1:2. The production of tetra‐ and pentacyclic scaffolds suggests that the reaction cavity for D‐ring formation site is somewhat loosely packed and can accept the 19‐ethyl group, and that a robust hydrophobic interaction exists between the 19‐ethyl group and the binding site. In contrast to19b, 10‐ethylsqualene20a and 15‐ethylsqualene20b afforded mainly mono‐ and bicyclic products, that is, the polycyclization cascade terminated prematurely at the bicyclic reaction stage. Therefore, the catalytic domains for the 10‐ and 15‐methyl binding sites are tightly packed and cannot fully accommodate the Et substituents. The cyclization pathways followed by the ethyl‐substituted substrates in the presence of SHC and lanosterol and β‐amyrin synthases are compared. Abstract : The cyclization of Et‐substituted squalenes (SQs) at C‐6, C‐10, C‐15, and C‐19 by squalene‐hopene cyclase has been studied. No reaction occurred with 6‐EtSQ, and mono‐ and bicyclic products were obtained with 10‐ and 15‐EtSQ. In contrast, 19‐EtSQ was converted into mono‐, bi‐, tetra‐, and pentacyclic products. The products give an insight into the binding in the recognition sites in the cyclase.